2023
DOI: 10.3390/app13074095
|View full text |Cite
|
Sign up to set email alerts
|

The C-3 Functionalization of 1H-Indazole through Suzuki–Miyaura Cross-Coupling Catalyzed by a Ferrocene-Based Divalent Palladium Complex Immobilized over Ionic Liquid, as Well as Theoretical Insights into the Reaction Mechanism

Abstract: The C-3 functionalization of 1H-indazole could produce a lot of highly valuable pharmaceutical precursors, which could be used for the treatment of cancer and many other inflammatory diseases. This work was focused on the C-3 functionalization of 1H-indazole through Suzuki–Miyaura cross-coupling of 3-iodo-1H-indazole with organoboronic acids, catalyzed by various palladium catalysts immobilized over imidazolium ionic liquids, as well as catalyst recycling. A series of reaction parameters, including the substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…From another point of view, the yield stemming from the protocol of Table 4 catalyzed by C2 (entry 12, Table 4; yield of 88%) was much higher than that from the same reaction catalyzed by PdCl 2 (dppf) (yield of 65%) [43]. Furthermore, C2 also showed a very close yield compared to the catalytic combination of PdCl 2 (dppf) with BMImPF 6 [45]. These results clearly indicate that the ball milling of the divalent palladium(II) precursor with silica gel produces a highly active palladium catalyst.…”
Section: Screening Of Catalystsmentioning
confidence: 93%
See 2 more Smart Citations
“…From another point of view, the yield stemming from the protocol of Table 4 catalyzed by C2 (entry 12, Table 4; yield of 88%) was much higher than that from the same reaction catalyzed by PdCl 2 (dppf) (yield of 65%) [43]. Furthermore, C2 also showed a very close yield compared to the catalytic combination of PdCl 2 (dppf) with BMImPF 6 [45]. These results clearly indicate that the ball milling of the divalent palladium(II) precursor with silica gel produces a highly active palladium catalyst.…”
Section: Screening Of Catalystsmentioning
confidence: 93%
“…It has been widely reported that the immobilization of palladium species into ionic liquid can provide more powerful catalysts for Suzuki-Miyaura cross-coupling, mainly because this kind of immobilization can increase the acidity of the palladium component, stabilize the active intermediate, inhibit the formation of non-catalytic palladium black, as well as improve catalyst recycling [45,46]. However, the suitable palladium components may be limited to homogeneous palladium salts or complexes rather than supported palladium materials.…”
Section: Effect Of Ionic Liquidmentioning
confidence: 99%
See 1 more Smart Citation
“…3-Iodoindazole was prepared according to literature procedures . A solution of 1 H -indazole (1 g, 8.4646 mmol), iodine (2 equiv), and potassium hydroxide (3.75 equiv) in DMF (5 mL) was stirred for 3 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%